P164 The Abyss Between Rcts And Guidelines; And The Bridging Role Of Cochrane Systematic Reviews. (15th August 2013) - Middleton, P; Crowther, C; Green, S
Abstract : Background: Randomised trials (RCTs) and Cochrane systematic reviews (CRs) are mainstays of most clinical practice guidelines (CPGs). It is important that all relevant high level evidence is included in CPGs. Objective: To determine rates of RCT inclusion in perinatal CPGs, either directly or via CRs. Methods: We used a database of all known Australian perinatal RCTs with findings released between 1986–2010 (n = 303), compiled for a project addressing impact of evidence. International and national perinatal CPGs were manually searched for cites of any of the 303 RCTs, or perinatal CRs including the RCTs, as at January 2013. Results: 59/303 RCTs (19%) were cited in at least one perinatal CPG. Ninety per cent of the 59 RCTs (n = 53) were included in CRs; and in 25/59 cases the RCT was only included in a CPG via the CR. All 59 included RCTs had a maternal/perinatal rather than a neonatal focus. Discussion: Over 80% of RCTs in this dataset were not included in relevant CPGs. The chance of a trial being in a CPG increased if was included in a CR and if it had a maternal/perinatal focus. Possible ways to close the RCT-CPG abyss will be presented. Implications for Guideline Developers/Users: While translation from RCT to CR is common, we need to better understand the reasons why high level RCT and CR evidence is often missing from CPGs and what the impact is on quality of CPG recommendations.